2020
DOI: 10.3390/ijms21082789
|View full text |Cite
|
Sign up to set email alerts
|

Biological Factors, Metals, and Biomaterials Regulating Osteogenesis through Autophagy

Abstract: Bone loss raises great concern in numerous situations, such as ageing and many diseases and in both orthopedic and dentistry fields of application, with an extensive impact on health care. Therefore, it is crucial to understand the mechanisms and the determinants that can regulate osteogenesis and ensure bone balance. Autophagy is a well conserved lysosomal degradation pathway, which is known to be highly active during differentiation and development. This review provides a revision of the literature on all th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 151 publications
0
28
0
Order By: Relevance
“…Previous studies have revealed that Aβ42 may affect cell autophagy in neurons (34)(35)(36), and defective autophagy has been reported in AD (37). Autophagy has also been found to be linked to osteogenesis (38)(39)(40). Therefore, we suspected that Aβ was able to regulate osteogenesis by altering autophagy in BMSCs.…”
Section: Endogenous Aβ Inhibited Osteogenesis and Autophagy In Bmscsmentioning
confidence: 89%
“…Previous studies have revealed that Aβ42 may affect cell autophagy in neurons (34)(35)(36), and defective autophagy has been reported in AD (37). Autophagy has also been found to be linked to osteogenesis (38)(39)(40). Therefore, we suspected that Aβ was able to regulate osteogenesis by altering autophagy in BMSCs.…”
Section: Endogenous Aβ Inhibited Osteogenesis and Autophagy In Bmscsmentioning
confidence: 89%
“… 42 Autophagy‐related components play a role in bone metabolism and bone diseases by regulating the survival and function of bone tissue cells. 43 , 44 , 45 , 46 , 47 There is increasing evidence that shows that osteoblast differentiation and maturation are stimulated by autophagic process. 44 , 48 It was also reported that endoplasmic reticulum stress is induced by defective autophagy in osteoblasts, resulting in significant bone loss.…”
Section: Discussionmentioning
confidence: 99%
“… 43 , 44 , 45 , 46 , 47 There is increasing evidence that shows that osteoblast differentiation and maturation are stimulated by autophagic process. 44 , 48 It was also reported that endoplasmic reticulum stress is induced by defective autophagy in osteoblasts, resulting in significant bone loss. 49 Recently, natural compound‐induced autophagy has been shown to enhance osteoblast differentiation and maturation, as well as ameliorate bone diseases.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing the activity of hFOBs is one of the keys to prevent and treat metabolic bone diseases. Therefore, hFOBs was selected as the subject cell in this study [ 16 , 17 ]. hFOBs (Chinese Academy of Medical Sciences, China) were cultured in Dulbecco Modified Eagle Medium (DMEM)/HAM F12 (Sigma-Aldrich, Dorset, UK) supplemented with 10% fetal bovine serum (FBS, Gibco), 1% triple antibiotic (penicillin, streptomycin, and amphotericin-B) (Solarbio), 0.6 mg/mL geneticin, and 2 mM l -glutamine (Gibco) at 37 ℃ temperature in a 5% CO 2 and a 95% humidified atmosphere for 2 days of incubation.…”
Section: Methodsmentioning
confidence: 99%